Experimental study to assess the effectiveness of moxibustion on nausea and vomiting in pregnancy - Fitria, Henni; Yulizawati, Yulizawati; Hudzaifah, Hindun Mila (Alma Ata University Press, 2025)
Background: Nausea and vomiting are common symptoms in pregnancy caused by hormonal changes. Although physiological, if not properly managed, these symptoms can lead to nutritional disturbances, dehydration, electrolyte imbalances, and hyperemesis gravidarum. Proper management is essential to alleviate nausea and vomiting and prevent pregnancy complications. Non-pharmacological methods are preferred to manage nausea and vomiting in pregnancy due to their lack of side effects. Objectives: This study aims to assess the impact of moxibustion on the P6 (Neiguan) and ST36 (Zusanli) acupoints on the incidence of nausea and vomiting during pregnancy. Moxibustion is known for its effectiveness in stimulating Qi at specific points that may be difficult to access through acupressure alone, thus improving the body's energy balancing process. The intervention is intended to improve pregnancy health outcomes.Methods: This study uses a quasi-experimental design with a pretest-posttest one-group framework to evaluate the effectiveness of moxibustion on nausea and vomiting during the first trimester of pregnancy. The participants consisted of 30 pregnant women selected using quota sampling based on inclusion criteria at selected independent midwifery practices. The instrument used was the Pregnancy Unique Quantification of Emesis (PUQE) to assess the intensity of nausea and vomiting in the respondents. Results: The results show a significant difference in the incidence of nausea and vomiting in the first trimester before and after moxibustion treatment (p < 0.05).Conclusions: Therefore, it can be concluded that moxibustion is beneficial in reducing nausea and vomiting symptoms during the early stages of pregnancy